USE OF ION ASSOCIATION COMPLEX FORMATION FOR THE SPECTROPHOTOMETRIC DETERMINATION OF ITOPRIDE HCL IN BULK AND ITS PHARMACEUTICAL PREPARATIONS - Rao, P. V. Lakshmana; Rambabu, C. (International Journal of Current Pharmaceutical Research, 2016)
Objective: The authors report two simple, accurate and economic spectrophotometric methods A and B for the determination of Itopride hydrochloride in bulk and dosage forms. Methods: The proposed methods are based on the formation of chloroform soluble ion-associates in the presence of acidic dyes namely BPB (Method A) and BCP (Method B) exhibiting lmax at 418 and 418 nm respectively. Results: Beer's law is found to be obeyed in the concentration range of 2.0-10.0 Âµg/ml and 2.0-10.0 Âµg/ml. The molar absorptivities are found to be 1.42x104 and 9.61x103L/mol. cm for methods A and B. These methods are successfully applied for the assay of Itopride hydrochloride in pharmaceutical formulations.